2011
DOI: 10.1038/onc.2011.322
|View full text |Cite
|
Sign up to set email alerts
|

An ErbB-3 antibody, MP-RM-1, inhibits tumor growth by blocking ligand-dependent and independent activation of ErbB-3/Akt signaling

Abstract: The ErbB receptors, such as ErbB-1 and ErbB-2, have been intensely pursued as targets for cancer therapeutics. Although initially efficacious in a subset of patients, drugs targeting these receptors led invariably to resistance, which is often associated with reactivation of the ErbB-3-PI3K-Akt signaling. This may be overcome by an ErbB-3 ligand that abrogates receptor-mediated signaling. Toward this end, we have generated a mouse monoclonal antibody, MP-RM-1, against the extracellular domain (ECD) of ErbB-3 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…Targeting EGFR or HER2 by antibody-mediated ubiquitination and degradation [24, 25, 27–29, 51] is one attractive way to improve therapeutic benefit in patients. Such mechanism has been also proposed for antibodies against HER3 [15, 50, 52, 53] or IGFR1 [54]. Pre-clinical studies using anti-HER3 antibodies clearly identified receptor degradation as a marker of drug efficacy [55].…”
Section: Discussionmentioning
confidence: 99%
“…Targeting EGFR or HER2 by antibody-mediated ubiquitination and degradation [24, 25, 27–29, 51] is one attractive way to improve therapeutic benefit in patients. Such mechanism has been also proposed for antibodies against HER3 [15, 50, 52, 53] or IGFR1 [54]. Pre-clinical studies using anti-HER3 antibodies clearly identified receptor degradation as a marker of drug efficacy [55].…”
Section: Discussionmentioning
confidence: 99%
“…It also significantly decreases colony formation in pancreatic cancer cells and tumor growth in pancreatic cancer, NSCLC, and colorectal cancer xenograft models [17]. Recently, a new anti-erbB3 Ab (MP-RM-1) and its humanized version (named EV20) both have been shown to exhibit antitumor activity against various cancer types in vitro and in vivo [93,94]. Because this Ab has the ability to inhibit both ligand-dependent and -independent activation of erbB3 [93,94], we speculate that EV20 may have a much broader effect on blocking erbB3 signaling than those Abs (like MM-121) which only prevent ligand-induced activation of erbB3, and thus exert more potent activity to overcome drug resistance in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of neurodegenerative disorders, L-Car has been suggested as an inhibitor of Ab toxicity in vitro (Preston et al 1998). Moreover, it has been reported that carnosine has a strong effect in restoring mitochondrial functioning and in counteracting amyloid pathology in triple-transgenic Alzheimer's disease model mice (Corona et al 2011). Very recently, a proteomic approach revealed that L-Car affects tumor cell growth by causing an interference with protein folding/processing and HIF-1a signaling in gliobastomas (Asperger et al 2011).…”
Section: Introductionmentioning
confidence: 98%